2021
DOI: 10.1186/s41938-021-00495-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of indigenous Bacillus thuringiensis isolates toxic to the diamondback moth, Plutella xylostella (L.) (Plutellidae: Lepidoptera)

Abstract: Background Toxins from the Bacillus thuringiensis (Bt) bacterium are employed as an alternative to synthetic pesticides in pest management. The greatest threat to the long-term viability of Bt toxins is resistance evolution in the target pests. Genetic diversity and toxicity of Bt isolates were studied in this work in order to find Bt isolates with novel cry genes. Results In terms of colony morphology, among a total of 60 isolates, 51 isolates had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
5
3
0
Order By: Relevance
“…PCR screening for lepidopteran toxic gene families confirmed the presence of cry1, cry1Ab, cry1Ac, cry2, cry2Aa, cry2Ab and vip3A genes in isolate T352 (Table 2). Various studies on indigenous Bt isolates revealed the cry1, cry1Aa, cry1Ab, cry1Ac, cry2Aa, cry2Ab and cry9 genes contributing the toxicity against major lepidopterous insects [24,[35][36][37][38] and the dominance of cry1 and cry2 gene existing together was usually high [39]. The Bt isolate T352 having cry1 and cry 2 along with vip3A gene and toxic to S. frugiperda was in agreement with previous studies [40].…”
Section: Pcr Screening Of Cry and Vip Genessupporting
confidence: 87%
See 1 more Smart Citation
“…PCR screening for lepidopteran toxic gene families confirmed the presence of cry1, cry1Ab, cry1Ac, cry2, cry2Aa, cry2Ab and vip3A genes in isolate T352 (Table 2). Various studies on indigenous Bt isolates revealed the cry1, cry1Aa, cry1Ab, cry1Ac, cry2Aa, cry2Ab and cry9 genes contributing the toxicity against major lepidopterous insects [24,[35][36][37][38] and the dominance of cry1 and cry2 gene existing together was usually high [39]. The Bt isolate T352 having cry1 and cry 2 along with vip3A gene and toxic to S. frugiperda was in agreement with previous studies [40].…”
Section: Pcr Screening Of Cry and Vip Genessupporting
confidence: 87%
“…Similarly, isolate GS4 tested by Patel and Ingle [33] against larvae of Helicoverpa armigera, showed multiple proteins in the range of 88, 54, 97, 175 and 135 kDa indicating the presence of more than one Cry protein and 12 Bt isolates effective against Spodoptera littoralis revealed the protein bands with different molecular weights in a range of 20-130 kDa [34]. Navya et al [35] studied protein profile in 60 indigenous Bt isolates and observed that variation in the molecular weight of Bt protein ranging from 26 to 124 kDa in size.…”
Section: Protein Profiling By Sds-page Analysismentioning
confidence: 96%
“…accordance with the earlier report by Navya et al (2021), confirming the presence of both cry and vip genes in combinations. Sahin et al (2018) revealed that vip3A1 positive isolates also had cry1 and cry2 genes, which are comparable to our findings.…”
Section: Insecticidal Gene Profilesupporting
confidence: 93%
“…There are protein bands of different molecular weights between 30 and > 200 kDa in size observed which need to be characterized. Diversified electrophoretic patterns in Cry protein with molecular weights ranging from 20 to 160 kDa were reported earlier by Navya et al (2021). In the present study, 16 isolates were found to produce one protein band (32.00%) and 16 isolates produce two protein bands (32.00%).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation